Clinical and prognostic significance of HIF-1α overexpression in oral squamous cell carcinoma: a meta-analysis - Jianhua Zhou; Shengyun Huang; Lili Wang; Xiao Yuan; Quanjiang Dong; Dongsheng Zhang; Xuxia Wang (World Journal of Surgical Oncology, 2017)
Abstract Background Recent studies have indicated an association between hypoxia inducible factor-1 alpha (HIF-1α) expression and poor prognosis in patients with oral squamous cell carcinoma (OSCC); however, definitive evidence of this association is yet to be obtained. We performed a meta-analysis to evaluate the association of HIF-1α expression with clinicopathological characteristics and overall survival (OS) of patients with OSCC. Methods A literature search for relevant studies published in English language as of February 05, 2016, was performed on PubMed, Web of Science, and EMBASE databases. Eighteen studies with a combined study population of 1474 patients with OSCC are included in the meta-analysis. Odds ratio (OR) or hazard ratio (HR) with 95% confidence interval (CI) was calculated using random-effects model or fixed-effects model. Results HIF-1α overexpression was significantly associated with larger tumor size (OR = 2.28, 95% CI = 1.49–3.50, P = 0.017), advanced TNM stage (OR = 2.29, 95% CI = 1.50–3.49, P = 0.158), and lymph node metastasis (OR = 2.05, 95% CI = 1.19–3.53, P < 0.001), but not with poor differentiation (OR = 1.21, 95% CI = 0.55–2.64, P = 0.024). These results demonstrated an association between HIF-1α expression and biological behavior of OSCC. On pooled analyses, high expression of HIF-1α was associated with worse OS (HR = 1.70, 95% CI = 1.10–2.61, P < 0.001). On subgroup analyses, overexpression of HIF-1α was significantly associated with poor prognosis in Asian population (HR = 2.33, 95% CI = 1.72–3.15, P = 0.862). Conclusions Our findings demonstrate an association of HIF-1α overexpression with tumor size, tumor stage, lymph node metastasis, and overall survival. HIF-1α could be an independent prognostic marker in patients with OSCC.